2020
DOI: 10.21203/rs.3.rs-76976/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COL1A1, COL1A2, COL3A1 and DCN are Potential Biomarkers to Predict Progression from Smokers to Suffering from Lung Adenocarcinoma

Abstract: Background: To explore novel related genes and potential biomarkers that predict progression from smokers to lung adenocarcinoma (LA). Methods: Three datasets from GEO (Gene Expression Omnibus) database were used to identify differentially expressed genes (DEGs) between LA tissue (LAT) and normal tumor adjacent tissue (TAT). The overlap of DEGs could be found and enriched in gene oncology (GO) and pathways to discover the potential biological mechanisms. Protein-protein interaction (PPI) network was applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Another study reported the expression of COL1A1, COL1A2, COL3A1 in blood and could be applied as predictive biomarkers in lung adenocarcinoma [36], which indicates the important role of this gene in many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported the expression of COL1A1, COL1A2, COL3A1 in blood and could be applied as predictive biomarkers in lung adenocarcinoma [36], which indicates the important role of this gene in many diseases.…”
Section: Discussionmentioning
confidence: 99%